Thematic Analysis of the Concept of Marital Jealousy among High-Conflict Couples - Samani, Hamideh; Goudarzi, Mahmoud; Moradi, Omid (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The objective of this study was to develop a model of marital jealousy reduction dimensions underlying jealousy regulation among couples. Methods and Materials: This qualitative study employed a thematic analysis approach to explore the lived experiences of high-conflict couples who reported successful jealousy reduction. Participants were selected through purposive sampling from family counseling centers, and data were collected using semi-structured in-depth interviews conducted until theoretical saturation was achieved. Interviews were transcribed verbatim and analyzed using an inductive–deductive coding strategy following Attride-Stirling’s thematic network model. MAXQDA software was used to manage and organize data. Trustworthiness was ensured through triangulation, negative case analysis, peer debriefing, member checking, and intercoder reliability assessment using Cohen’s kappa coefficient. Findings: The analysis yielded a four-dimensional model of marital jealousy reduction consisting of individual, dyadic, familial, and social dimensions. Each dimension comprised several principal themes that interacted in a dynamic, circular pattern. Individual factors included emotional self-regulation, optimistic meaning-making, spiritual orientation, personal growth, and mature defense mechanisms. Dyadic processes involved marital satisfaction, intimate communication, compassionate commitment, adaptive stress management, sexual enrichment, and constructive engagement with external relationships. Familial influences encompassed supportive conflict management, emotional and material backing, healthy family-of-origin functioning, and strong endorsement of marital stability. Social determinants included public awareness, access to professional counseling services, and broader socioeconomic conditions. Conclusion: Marital jealousy reduction emerges as a complex systemic process shaped by reciprocal interactions across personal, relational, familial, and societal levels, underscoring the necessity of integrated, multilevel interventions in both clinical practice and social policy.